Perioperative Mortality Risk in Patients Undergoing Transoral Robotic Surgery for T1-T2 Oropharyngeal Squamous Cell Carcinoma: A National Cancer Database Study - Davies, Joel C.; Husain, Zain; Day, Terry A.; Graboyes, Evan M.; Eskander, Antoine (Frontiers in Oncology, 2022)
Introduction: Transoral robotic surgery (TORS) is well established as initial definitive treatment for early-stage oropharyngeal squamous cell carcinoma (OPSCC) as an alternative to radiation therapy with similar survival rates. While proponents of TORS focus on the reduced morbidity of treatment compared to open procedures, shortened hospital admissions and equivalent survival outcomes to non-surgical treatment, there remain concerns over the risk of mortality within the acute perioperative period. Therefore, we sought to determine the 30-day and 90-day perioperative mortality risk using the National Cancer Database. Methods: A retrospective cohort analysis was performed for patients diagnosed with pathologic T1/2 OPSCC between January 1, 2010, and December 31, 2016 that underwent primary surgical treatment with TORS and was not restricted by HPV status. The primary outcome was 30-day perioperative mortality. The secondary outcome was 90-day perioperative mortality. Univariable analysis was used to identify variables associated with 30-day perioperative mortality. Results: In total, 4,127 patients (mean [SD; range] age, 59 [9.5; 22-90] years; 3,476 [84%] men and 651 [16%] women) met inclusion criteria. The number of patients with pT1-2 OPSCC undergoing TORS increased three-fold between 2010 (279/4,127; 7%) to 2016 (852/4,127; 21%). The overall 30-day and 90-day perioperative mortality rate for TORS during the study period was 0.6% (23/4,127) and 0.9% (38/4,127), respectively. On univariable analysis (UVA), age≥65 was the only predictor of 30-day perioperative mortality (OR 3.41; 95% CI 1.49-7.81). Conclusion: The overall risk of all cause mortality following TORS for early-stage OPSCC remains low. The risk of mortality is higher in elderly patients and should be considered, in addition to previously established risk factors, during patient selection and counselling.